Stay-at-Home Orders, Social Distancing and Trust - Abel Brodeur; Idaliya Grigoryeva; Lamis Kattan (Global Labor Organization (GLO), 2020)
Better understanding whether and how communities respond to government decisions is crucial for policy makers and health offcials in response to the COVID-19 pandemic. In this study, we document the socioeconomic determinants of COVID-19 stay-at-home orders' compliance in the U.S. Using cell phone data measuring changes in average distance traveled and non- essential visitation, we find that: stay-at-home orders reduce mobility by about 810 percentage points; high-trust counties decrease their mobility significantly more than low-trust counties post-lockdown; and counties with relatively more self-declared democrats decrease significantly more their mobility. We also provide evidence that the estimated effect on compliance post-lockdown is especially large for trust in the press, and relatively smaller for trust in science, medicine or government.
Keywords: H12; I12; I18; 330; COVID-19; stay-at-home orders; social distancing; trust